Investment Feasibility Analysis of Container Depot for Sustainable Development: A Case Study on PT. Pelabuhan Indonesia (Persero): Analisis Kelayakan Investasi Depo Peti Kemas untuk Pembangunan Berkelanjutan: Studi Kasus pada PT. Pelabuhan Indonesia (Persero) - Soedarmanto; Fail, Moh; Artnasoni, Annisa Balqis (Universitas Muhammadiyah Sidoarjo, 2023)
This research aims to analyze the feasibility of container depot investment as a sustainable development objective on the independent variables for the revenue of PT. Pelabuhan Indonesia (Persero) as the dependent variable. The study utilizes secondary data obtained from the company. A descriptive quantitative method and business feasibility analysis technique are employed, considering legal, market and marketing, economic and environmental, technical, management, and financial aspects. The analysis includes Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). The research findings conclude that the feasibility analysis of the container depot contributes to the revenue of PT. Pelabuhan Indonesia (Persero) Regional Jawa. However, revenue sharing has minimal impact on the income of the Property Division and Miscellaneous Business Division compared to lease cooperation. The study suggests that the investment allocation through revenue sharing is more optimal and effective, provided the throughput remains stable. It highlights the importance of thorough analysis and stable market conditions for successful investment decisions in the container depot industry. Highlight: The feasibility analysis of container depot investment contributes to the revenue of PT. Pelabuhan Indonesia (Persero) Regional Jawa. Revenue sharing has minimal impact on the income of the Property Division and Miscellaneous Business Division compared to lease cooperation. The allocation of investment in the container depot can be more optimal and effective through revenue sharing, provided that the throughput conditions remain stable. Keyword: Investment, Container Depot, PT Pelabuhan Indonesia, Feasibility Analysis, Revenue Sharing.